1983
DOI: 10.1182/blood.v62.5.996.996
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor analysis in chronic lymphocytic leukemia

Abstract: Estrogen receptor (ER) determinations were performed on cytosol preparations of Ficoll-Hypaque density separated mononuclear cells from 11 patients with chronic lymphocytic leukemia (CLL). The presence of ER was noted in 8 of 11 specimens (73%). ER ranged from 431 fmole/mg to 4.3 fmole/mg cytosol protein. Two types of receptor subunits were observed at the 8S and 4S region of the sucrose gradient. In addition, 1 of 3 Epstein-Barr virus (EBV) transformed B-lymphoblastoid cell lines from healthy donors had a mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Sex hormones exert their influence via hormone-specific receptors. For estrogens, some studies support the expression of estrogen receptors (ERs) in CLL but with variable results [ 8 10 ] with more recent data pointing towards a predominance of ERβ [ 11 ]. Hormone receptors like ERβ are ligand-regulated transcription factors activated by naturally produced steroid hormones that regulate transcription of genes controlling a wide variety of biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Sex hormones exert their influence via hormone-specific receptors. For estrogens, some studies support the expression of estrogen receptors (ERs) in CLL but with variable results [ 8 10 ] with more recent data pointing towards a predominance of ERβ [ 11 ]. Hormone receptors like ERβ are ligand-regulated transcription factors activated by naturally produced steroid hormones that regulate transcription of genes controlling a wide variety of biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Methylation levels were also low for these genes with the exception of HIC-1 (Figure 2). Estrogen receptor (ER) is often silenced in breast cancer; however, it is not always silenced in leukemias [16]. Similarly, GSTP1 is epigenetically silenced in prostate cancers, but its expression correlation with leukemia is not well defined [17].…”
Section: Discussionmentioning
confidence: 99%
“…In estrogen-dependent breast cancer, ER is expressed in 70%–80% breast cancer cells but in only 15%–25% normal breast cells. Several clinical experiments have confirmed that ERs are overexpressed in endometrial cancer, laryngeal cancer, ovarian cancer, lung cancer and other tissues [10] , [11] , [12] , [13] . At present, various nanodelivery systems targeting ERs have been developed, and the targeting ligands used mainly include estradiol [14] , estrone [15] , tamoxifen [16] and endoxifen [17] .…”
Section: Introductionmentioning
confidence: 96%